Association Between Serum Hepcidin Levels and Anemia in Patients with Rheumatoid Arthritis: A Case-Control Study - Mahdi, Doaa Faleh; Shwayel, Ameer Jabbar (Medical Science Journal for Advance Research, 2025)
Background: Anemia is a prevalent comorbidity in rheumatoid arthritis (RA), primarily classified as anemia of chronic disease (ACD). Hepcidin, an iron-regulatory hormone induced by inflammation, is a key mediator in ACD pathogenesis, but its relationship with RA-specific autoimmunity remains to be fully elucidated. Objective: This study aimed to investigate the role of circulating hepcidin in RA-related anemia and its correlation with disease activity markers, including anti-cyclic citrullinated peptide (anti-CCP) antibodies. Materials and Methods: A case-control study was conducted from April to June 2025, comprising 50 newly-diagnosed RA patients and 50 healthy controls. Venous blood samples were collected to measure hematological parameters (hemoglobin, WBC), iron profiles (iron, ferritin), inflammatory biomarkers (CRP), RA serology (rheumatoid factor, anti-CCP), and serum hepcidin levels using ELISA and automated immunoassays. Results: RA patients exhibited significantly lower hemoglobin and serum iron levels, and significantly higher WBC, CRP, RF, anti-CCP, and hepcidin levels compared to controls (p < 0.001). Serum ferritin did not differ significantly. Patients with high anti-CCP levels (≥100 AU/mL) had significantly elevated hepcidin, CRP, RF, and WBC, and lower serum iron, indicating a strong association between anti-CCP titer, inflammatory activity, and iron dysregulation. Conclusion: Elevated hepcidin is significantly associated with anemia in RA patients. Levels of anti-CCP strongly correlate with increased inflammatory activity and hepcidin expression, suggesting that anti-CCP may be a useful marker for identifying RA patients with more active disease and a greater risk of developing hepcidin-mediated anemia.